Ольвія: проблеми охорони та археологічні дослідження - Крапівіна, В.В. (Археологія, 2001)
У статті розглянуто стан збереженості античної Ольвії з кінця XVIII ст. донині, розвиток справи ії охорони та основні етапи археологічного дослідження. В статье рассматривается состояние античной Ольвии от момента присоединения к России южных земель и идентификации памятника до настоящего времени. До рубежа XIX—XX вв. состояние Ольвии характеризуется эпизодическими археологическими исследованиями, массовыми хищническими раскопками и выборками камня. Ситуация изменяется только с началом систематических раскопок Ольвии в начале XX в. Б. В. Фармаковским. Отрицательно отразились на памятнике обе мировые войны и послереволюционное время. История собственно заповедника «Ольвия» может быть разделена на три периода: 1926—1938 гг. — зарождение основных структур заповедника; 1938—1971 гг.— развитие основных научных и организационных форм и направлений его деятельности; 1972 — настоящее время — дальнейшее развитие структуры заповедника и усложнение выполняемых им научных задач, переход к научным темам по консервации и частичной реставрации архитектурных остатков. Успешное функционирование заповедника в значительной степени определяется его сотрудничеством с Ольвийской экспедицией ИА НАН Украины. В последние годы в связи с сокращением финансирования заповедника резко возросло отрицательное воздействие антропогенного фактора (грабительские раскопки, вандализм). Спасение Ольвии — уникального памятника мировой культуры — невозможно без государственной поддержки. The article deals with the condition of antique Olbia from the moment of joining the southern lands to Russia and identifies the monument to this day. Till the boundary of the XIX-XX centuries, episodic archaeological investigations, mass destructive excavations, and exceptions to stone characterized the condition of Olbia. The situation changed only with the beginning of systematic excavations of Olbia, held by B. V. Farmakovskiy at the start of the XX century. The new posts of inspectors and guards of the town’s territory and the vault of Evrisiviy and Aretha were set up. The post-revolutionary time and both the World Wars had a very negative impact on the monument. The history of the preserve «Olbia» itself may be divided into three periods. The first period (1926–1938) — from the moment of the declaration of the territory of Olbia the state preserved and transmitted it to the system of the Academy of Sciences of the Ukrainian SSR. This period is characterized by the origin of the basic structures of the preserve. The II period (1938–1971) is connected with the activity of the head of the Olbian expedition, L. M. Slavin. The development of the basic scientific and organizational forms and directions of their activity characterizes it. The III period (1972 — to this day) is characterized by the subsequent development of the preserve’s structure and complication of the scientific aims to be fulfilled, the transmission of scientific topics on conservation, and the partial restoration of the architectural remnants. The preserve’s successful functioning is mainly defined by its collaboration with the Olbian expedition of the Institute of Archaeology of the National Academy of Sciences of Ukraine. The reduction in the financing of the preserve in recent times has caused a definite increase in the negative influence of the anthropogenic factor (robbery excavations, vandalism). The salvation of Olbia — the unique monument of the world’s culture, is impossible without state support.